Cost effectiveness of intermittent screening followed by treatment versus intermittent preventive treatment during pregnancy in West Africa: analysis and modelling of results from a non-inferiority trial. (December 2016) - Fernandes, Silke; Sicuri, Elisa; Halimatou, Diawara; Akazili, James; Boiang, Kalifa; Chandramohan, Daniel; Coulibaly, Sheikh; Diawara, Sory; Kayentao, Kassoum; Kuile, Feiko; Magnussen, Pascal; Tagbor, Harry; et al.
Abstract Background Emergence of high-grade sulfadoxine-pyrimethamine (SP) resistance in parts of Africa has led to growing concerns about the efficacy of intermittent preventive treatment of malaria during pregnancy (IPTp) with SP. The incremental cost-effectiveness of intermittent screening and treatment (ISTp) with artemether-lumefantrine (AL) as an alternative strategy to IPTp-SP was estimated followed by a simulation of the effects on cost-effectiveness of decreasing efficacy of IPTp-SP due to SP resistance. The analysis was based on results from a multi-centre, non-inferiority trial conducted in West Africa. Methods A decision tree model was analysed from a health provider perspective. Model parameters for all trial countries with appropriate ranges and distributions were used in a probabilistic sensitivity analysis. Simulations were performed in hypothetical cohorts of 1000 pregnant women who received either ISTp-AL or IPTp-SP. In addition a cost-consequences analysis was conducted. Trial estimates were used to calculate disability-adjusted-life-years (DALYs) for low birth weight and severe/moderate anaemia (both shown to be non-inferior for ISTp-AL) and clinical malaria (inferior for ISTp-AL). Cost estimates were obtained from observational studies, health facility costings and public procurement databases. Results were calculated as incremental cost per DALY averted. Finally, the cost-effectiveness changes with decreasing SP efficacy were explored by simulation. Results Relative to IPTp-SP, delivering ISTp-AL to 1000 pregnant women cost US 4966.25 more (95 % CI US 3703.53; 6376.83) and led to a small excess of 28.36 DALYs (95 % CI −75.78; 134.18), with LBW contributing 81.3 % of this difference. The incremental cost-effectiveness ratio was −175.12 (95 % CI −1166.29; 1267.71) US/DALY averted. Simulations show that cost-effectiveness of ISTp-AL increases as the efficacy of IPTp-SP decreases, though the specific threshold at which ISTp-AL becomes cost-effective depends on assumptions about the contribution of bed nets to malaria control, bed net coverage and the willingness-to-pay threshold used. Conclusions At SP efficacy levels currently observed in the trial settings it would not be cost-effective to switch from IPTp-SP to ISTp-AL, mainly due to the substantially higher costs of ISTp-AL and limited difference in outcomes. The modelling results indicate thresholds below which IPT-SP efficacy must fall for ISTp-AL to become a cost-effective option for the prevention of malaria in pregnancy.